Universal Features of Personality Traits from the Observer’ s Perspective: Data from 50 Cultures - McCrae, Robert (Array, 2005)
To test hypotheses about the universality of personality traits, college students in 50 cultures identified an adult or college-age man or woman whom they knew well and rated the 11, 985 targets using the third-person version of the Revised NEO Personality Inventory. Factor analyses within cultures showed that the normative American self-report structure was clearly replicated in most cultures, and was recognizable in all. Sex differences replicated earlier self-report results, with the most pronounced differences in Western cultures. Cross-sectional age differences for three factors followed the pattern identified in self-reports, with moderate rates of change during college age and very slow changes after age 40. With a few exceptions, these data support the hypothesis that features of personality traits are common to all human groups.